CRIME OF EXPLOITATION CRIME ANALYSIS OF CHILD WORK AS HOUSEHOLD SERVICE - Ria Desna Anggraini (Ius Poenale, 2022)
Law Number 35 Article 1 paragraph 6 of 2014 concerning Child Protection is a criminal law policy to protect children who are exploited, sexually assaulted, or employed as housemaids. The issues discussed in this article pertain to the factors that contribute to the occurrence of criminal acts of exploitation of children employed as housemaids, as well as the prevention of criminal acts of exploitation of children employed as housemaids. The research method used was normative juridical and empirical juridical. Data collection was done through literature study and field study, while the data obtained were analyzed qualitatively. Based on the results of research and discussion, economic problems, bad environmental influences, low education, social factors, lack of public and government awareness, being easily deceived, weak parental supervision, and weak law enforcement are among the factors that encourage the exploitation of children employed as housemaids. Efforts to tackle the crime of child exploitation as domestic helpers consist of pre-emptive, preventive, repressive, and rehabilitation efforts.